Big data analysis with Python combine Spark and Python to unlock the powers of parallel computing and machine learning - Marin, Ivan (Packt Publishing, 2019)
Processing big data in real time is challenging due to scalability, information inconsistency, and fault tolerance. Big Data Analysis with Python teaches you how to use tools that can control the data avalanche for you. With this book, you'll learn effective techniques to aggregate data into useful dimensions for posterior analysis, extract ...